Relationship Among Ethical Value And Fraud Diamond In Banking Industry During Pandemic - Putri WULANDITYA; Herwin ARDIANTO; Evi SISTIYARINI (Indonesia Strategic Sustainability, 2022)
The occurrence of an economic crisis and the company's operating conditions that are different from usual during the pandemic can result in the emergence of loopholes in committing fraud. This study aims to investigate the relationship between ethical values and the fraud diamond, namely, pressure, opportunity, rationalization, and capability against bank employee fraud during the pandemic. Thus, this research is expected to make a theoretical contribution to the development of fraud theory and a practical contribution to policymakers in preventing fraud in the banking industry. The methods research is a quantitative study with primary data sourced directly from online survey responses. The respondents of this research are followed by 133 bank employees in Indonesia. Based on the Rank Spearman Correlation test, the factors that significantly influence bank employee fraud during the pandemic are ethical values, opportunity, rationalization, and capability. Pressure has no significant effect on bank employee fraud. Furthermore, rationalization has a significant relationship with all variables tested, especially on capabilities, ethical values, and employee fraud. These results suggest that the banking industry anticipates wrong rationalizations from employees regarding fraudulent acts. Instilling ethical values is believed to be able to direct the right rationalization so that employees do not take advantage of their abilities to commit fraud in the workplace.